2013
DOI: 10.1590/s0100-67622013000200007
|View full text |Cite
|
Sign up to set email alerts
|

Valoração econômica da área de proteção ambiental estadual da Cachoeira das Andorinhas - MG

Abstract: A valoração econômica dos ativos ambientais é importante critério que subsidia a tomada de decisões na definição de políticas que gerenciam os recursos naturais. Nesse sentido, buscou-se valorar a Área de Proteção Ambiental Estadual da Cachoeira das Andorinhas (APAE/CA), importante Unidade de Conservação do Município de Ouro Preto, MG, com 18.700 ha de extensão. Apesar de possuir importante patrimônio natural, tal ativo ambiental possui áreas degradadas, além de ainda não ter o respaldo necessário dos órgãos g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 8 publications
0
3
2
11
Order By: Relevance
“…Previous studies have reported that married and divorced couples, households with a high number of people, low-income households, and unemployed people tend to be less willing to contribute to environmental conservation proposals (Cirino & Lima 2008;Silveira et al 2013). We found no statistical differences among respondents with different household sizes, incomes, occupations, and marital status, and even between those who reported depending (or not) financially on harvesting palm leaves (Tabs.…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…Previous studies have reported that married and divorced couples, households with a high number of people, low-income households, and unemployed people tend to be less willing to contribute to environmental conservation proposals (Cirino & Lima 2008;Silveira et al 2013). We found no statistical differences among respondents with different household sizes, incomes, occupations, and marital status, and even between those who reported depending (or not) financially on harvesting palm leaves (Tabs.…”
Section: Resultscontrasting
confidence: 51%
“…1, 2). People with higher levels of education are believed to have a better understanding of the negative effects of human interference in the environment, with consequently higher levels of WTP (Morgado et al 2011;Silveira et al 2013). However, we found no significant differences in the levels of WTP of respondents with different levels of education (Tabs.…”
Section: Resultscontrasting
confidence: 44%
“…The Indirect Method of Contingent Valuation (MAC) makes use of statistics public consultations, such as interviews, to directly capture the individual values of use and non-use, assigned to a natural resource (Silveira et al, 2013).The questioning may be voluntary like the willingness to pay (WTP), or induced like multiple choice quizzes (DA COSTA et al, 2015).It is required, however, special care in planning and execution of research so that it does not direct the results and compromise the analysis of the estimates (PALMER, MAIA, 2011).However, it is recommended to have caution in the use of environmental valuation methods, and the combined use of other nonmonetary criteria of environmental impact assessment, as Templates Decision Support, or Multi-criteria (MCDA -Multiple Criteria Decision Aid), especially when the impact or environmental resource can become irreversible (Pearce, 1993; Andrade and Romeiro, 2011; Ribeiro, 2015; Leal Jr. and D'Agosto, 2012).…”
Section: Environmental Valuation Methodsmentioning
confidence: 99%
“…The population growth and the industrialization generated several negative impacts in the environment and the world, bringing considerable damage to ecosystems, uncertainty of resources to future generations and climate changes (SILVEIRA; CIRINO; PRADO FILHO, 2013). Those problems are directly related to the environmental and life quality of their populations (NASCI-MENTO; RIBEIRO;SOUSA, 2013).…”
Section: Introductionmentioning
confidence: 99%